Pre-eclampsia Complicated With Maternal Renal Dysfunction Is Associated With Poor Neurological Development at 3 Years Old in Children Born Before 34 Weeks of Gestation - Yoneda, Noriko; Yoneda, Satoshi; Tsuda, Sayaka; Ito, Mika; Shiozaki, Arihiro; Niimi, Hideki; Yoshida, Taketoshi; Nakashima, Akitoshi; Saito, Shigeru (Frontiers in Pediatrics, 2021)
Objective: The purpose of this study was to investigate perinatal factors associated with a poor neurodevelopmental outcome in preterm infants. Methods: A retrospective study was conducted by searching our clinical database between January 2006 and December 2016. A total of 165 singleton children who were born between 23 and 33 weeks of gestation were included. We defined poor neurological development outcomes as follows: cerebral palsy, mental retardation, developmental disorder including autism and attention deficit hyperactivity disorder, low score (<85 points) on Bayley Scales of Infant and Toddler Development, Third Edition (Bayley−III), or low score of Kyoto Scale of Psychological Development corrected at 3 years old. We diagnosed maternal renal dysfunction according to the Clinical Practice Guideline for chronic kidney disease 2018 and the Best Practice Guide 2015 for Care and Treatment of Hypertension in Pregnancy. Results: The rate of poor neurological development was 25/165 (15.2%): cerebral palsy (n = 1), mental retardation (n = 1), developmental disorder (n = 2), low score of Bayley−III (n = 20), and low score of Kyoto Scale of Psychological Development (n = 1). Preeclampsia (PE) complicated with maternal renal dysfunction (P = 0.045), and delivery at less than 30 weeks of gestation (P = 0.007) were independent risk factors for poor neurological development. Conclusions: In addition to previous risk factors such as delivery at less than 30 weeks of gestation, preeclampsia complicated with renal dysfunction was also associated with poor neurodevelopmental outcomes corrected at 3 years old.